HUBUNGAN POLA ASUH ORANG TUA DENGAN KOMPETENSI ANAK USIA DINI (4-6 TAHUN) DI RA BAITUL MUTTAQIN KABUPATEN JEMBER - Hasanah, Nur; Sary, Yessy Nur Endah; Lestari, Dwi Anggun (NHM PRESS, 2024)
The importance thing is that children aged 4-6 years have competence, namely preparing themselves for the future where in the future children can compete with the outside world. The purpose of this study was to analyze the correlation between parenting style and competence of early childhood (4-6 years) at RA Baitul Muttaqin, Jember. This study used a correlation design with a cross sectional approach. The population in this study were 43 children. The sampling technique used is Total Sampling. Data was collected using data collection sheets. Data were analyzed using SPSS with chi square test at a significance level of α<0.05. The results showed that 13 respondents (30,2%) had democratic parenting styles with good competence, 11 (25.6%) authoritarian parenting styles were sufficient, and 2 (4,6%) were permissive parenting styles with less competence. Based on the results of the analysis, it is known that there is a correlation between parenting style and early childhood competence (4-6 years) in RA Baitul Muttaqin, Jember p-Value=0.004 (α<0.05). Suggestions for midwifery services are expected to be able to provide socialization regarding parenting so that competence can develop properly.